Mekanisme Penghimpunan dan Penyaluran Dana dalam Bank Syariah dan Konvensional: Tinjauan Fatwa DSN-MUI dan Regulasi Perbankan - Asa Zahrani; Salis Azkia; Hali Hali; Muhammad Aryandhi Fikri; Joni Joni; Raihani Fauziah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article analyzes the fundamental differences between the mechanisms of fund collection and fund distribution in Islamic banks and conventional banks in Indonesia, based on DSN-MUI Fatwas and banking regulations. In general, both types of banks serve the same function—to collect and distribute funds to support economic activities. However, the main distinction lies in their operational principles. Conventional banks operate using a fixed interest system, establishing a creditor–debtor relationship. In contrast, Islamic banks operate based on Sharia principles that prohibit riba (usury). In fund collection, conventional banks use interest-based savings and deposit products, while Islamic banks apply Wadiah (safekeeping) and Mudharabah (profit-sharing investment) contracts. Regarding fund distribution, conventional banks provide interest-bearing loans, whereas Islamic banks offer financing through Sharia contracts such as Murabahah (cost-plus sale), Musyarakah (partnership), Mudharabah (profit-sharing), and Ijarah (leasing), emphasizing cooperation and risk-sharing. Although Islamic banking is regulated under Law No. 21 of 2008 and DSN-MUI Fatwas, it still faces several challenges, including the dominance of Murabahah financing and the low level of public literacy regarding Islamic financial systems.